2001
DOI: 10.1152/jappl.2001.91.6.2471
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical response to acupuncture needling in humans

Abstract: During acupuncture treatments, acupuncture needles are manipulated to elicit the characteristic "de qi" reaction widely viewed as essential to acupuncture's therapeutic effect. De qi has a biomechanical component, "needle grasp," which we have quantified by measuring the force necessary to pull an acupuncture needle out of the skin (pullout force) in 60 human subjects. We hypothesized that pullout force is greater with both bidirectional needle rotation (BI) and unidirectional rotation (UNI) than no rotation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 210 publications
(139 citation statements)
references
References 22 publications
4
130
1
2
Order By: Relevance
“…Moreover, there was a greater pullout force following uni-and bidirectional winding compared to needle insertion without manipulation [77,78]. By using trichrome staining, Langevin further demonstrated that pullout force is due to the mechanical coupling of collagen fibers to the needle [77].…”
Section: The Physiology and Relevance Of Needle Mechanotransductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, there was a greater pullout force following uni-and bidirectional winding compared to needle insertion without manipulation [77,78]. By using trichrome staining, Langevin further demonstrated that pullout force is due to the mechanical coupling of collagen fibers to the needle [77].…”
Section: The Physiology and Relevance Of Needle Mechanotransductionmentioning
confidence: 94%
“…Through a series of elegant studies, Langevin et al found that a greater pullout force is required to remove a needle from tissue when the needle is wound in one direction compared to when it is wound in both directions [76,78]. Moreover, there was a greater pullout force following uni-and bidirectional winding compared to needle insertion without manipulation [77,78].…”
Section: The Physiology and Relevance Of Needle Mechanotransductionmentioning
confidence: 99%
“…Some practitioners of acupuncture refer to de-qi as "needle grasp, " a biomechanical phenomenon characterized by an increase in the force necessary to pull the needle out of the tissue. It has been proposed that the sensation of needle grasp is due to the contraction of skeletal muscle [126] or winding of connective tissue around the needle during needle rotation [127]. By using electric impedance, Lin showed that muscle layers were the major site of de-qi in the 22 acupoints in the back [128].…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicate a relationship among APs and myofascial trigger points [14,15], connective tissue planes [16], and nerve-vessel bundles penetrating the superficial fasciae [17]; however, given the high occurrence of these structures, it remains unclear which of them are specific for APs. A significantly larger needle grasp [18] and larger blood supply into the microvascular beds [19] at APs when compared to other areas has been observed. Additionally, conflicting results also exist about APs being spots characterized by a high density of neural receptors [20,21] or a distinct electrical skin resistance [22][23][24].…”
Section: Introductionmentioning
confidence: 93%